REHABILITASI ANAK PECANDU NARKOBA DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Hardiman, Setiaki (Universitas Islam Negeri Raden Fatah Palembang, 2020)
Legal protection for children victims of narcotics abuse is the right of every child, therefore it is an obligation for parents, society and the government to provide protection for children. Thus, the purpose of this study was to determine the process of implementing narcotics rehabilitation involving child drug addicts at the BNN in South Sumatra Province. The second objective is to analyze the implementation of rehabilitation of children with narcotics addicts according to Islamic criminal law. This research is a field research conducted at BNN South Sumatra Province. Data collection techniques through observation, interviews and documentation. Then the data that has been collected is analyzed descriptively qualitatively, and deductive conclusions are drawn. Based on the results of the study, it shows that: First, the process of implementing narcotics rehabilitation involving child drug addicts at the South Sumatra National Narcotics Agency is in accordance with what is mandated by the Law on Narcotics and the Child Protection Act. As it is known that the rehabilitation center has done its job well, in rehabilitation it is not only social and medical rehabilitation, but also self-development and recreation accompanied by therapeutic remedies for narcotics addicts. Second, there are several obstacles in implementing rehabilitation for children who are narcotic addicts, namely the lack of knowledge of the community, especially families of narcotics addicts, and there are also families who do not know how to report to the BNN. Please also note that all of this rehabilitation is free of charge because the costs are borne by the ministry of health. Keywords: rehabilitation, narcotics addicts, child narcotics